The Impact of Pipe Ø 0,5 Heater Length and Temperature on Ovality and The Difference in Pipe Thickness for Its Bending - Musholli Musholli; Sudarmaji Sudarmaji (Logic, 2023)
Abstract,  Ferrous metal is of material utilized mostly for many objects or kinds of stuff to help humans and their work easier. Low-carbon steel is one of the ferrous metal natures that could be utilized when transforms into more useful objects. There be cold as well as hot working to undertake. Molting by bending pipe includes cold working due to it being bent as its recrystallization temperature is lower.